"Permanence with Accountability": An Elusive Goal of the NPT. Issue 2 (2nd July 2020) - Meyer, Paul
ABSTRACT: The slogan "permanence with accountability" emerged at the NPT's 1995 Review and Extension Conference as a way of characterizing the outcome of that conference – the indefinite extension of the treaty coupled with enhanced means of ensuring accountability for the implementation of its provisions. Today some 25 years later, the validity of this concept is in question. Consistent efforts by the non-nuclear weapon states party to the NPT to persuade the treaty's five nuclear weapon states to be more forthcoming in reporting to the NPT membership on their implementation of nuclear disarmament commitments has yielded little progress. Even the modest goal of accepting a standardized reporting format and periodicity for submitting implementation reports has eluded supporters. In the absence of a detailed and comparable data base how can NPT states parties effectively hold nuclear weapon states accountable? Amid the other serious stresses on the NPT in the leadup to its next Review Conference, a failure to address the long-standing plea for greater transparency as a prerequisite for accountability could sap the treaty of much of its remaining authority.